Fatores decisórios na sucessão geracional dos filhos de associados de cooperativas agropecuárias - Amorim, Gabrieli dos Santos (2020)
Young rural population has been made vulnerable to migrating from rural to urban in the pursuit of tending to their professional and personal necessities, therefore promoting rural exodus which leads to diverse consequences, such as masculinization, aging of rural population, the lack of generational succession and absence of qualified labor. The lack of generational succession is the framework which sustains this study in analyzing the decisive succession factors that influence on the generational succession processes of cooperative associate’s children in cooperatives that operate on the segments of grains, meat and milk in the state of Rio Grande do Sul. A number of 25 decisive factors have been analyzed by the perspective of young successors and the agricultural cooperatives’ staff. The methodology utilized is classified as a research of mixed qualitative and quantitative approaches, utilizing an interview form as instrument of data collection. The interview form was applied to a total sample of 308 young successors at the age range between 18 and 30 years old and to one staff member of each agricultural cooperative, during the period of July to November 2019. As such, the decisive factors’ degree of importance and performance were analyzed, employing the adapted methodology of Slack, Chambers and Johnston (2007), called the importance-performance matrix, which analyzes the factors based on four zones of priority improvements. Beyond assessing the decisive factors and availing the determinant ones in the permanence of the rural youth on the fields, the study sought to help agricultural cooperatives on the formulation of strategies so the rural youth remains on the rural areas guaranteeing the future social continuity of the cooperative associates existence. Results have pointed that the majority of the young is composed of single males working on rural properties’ productive activities. Regarding the decisive factors, in the opinion of the young successors belonging to the meat segment cooperative, factors that need improvement are the social valuing of the farmer and the price of the agricultural products. In the milk segment cooperative, decisive factors in need of improvement are leisure infrastructure within the rural community, social valuing of the farmer and the price of the agricultural product, highlighting roads infrastructure as the factor that needs urgent improvement. In the grains cooperative, the decisive factors needing improvement are leisure structure within the rural community, roads infrastructure, social valuing of the farmer, agricultural products’ price, rural credit and public policies. Regarding the decisive factors in the opinion of the cooperative’s staff, none of the decisive factors need improvement in meat segment cooperative, however 48% of the factors in the grains cooperative and 68% in the milk cooperative do need improvement. It has been observed that both the young successors and the agricultural cooperatives share common opinions about the decisive factors. Ergo, it’s relevant that the cooperatives aim to comprehend the decisive factors that need enhancement and seek to perfect them, especially those with performance rating below the importance level.